Kyai Policy Implementation in Improving Teacher Performance in Darul Muttaqien Bogor Pondok - Nunung Kurniasih; R. Supyan Sauri; Ujang Cepi Barlian (International Journal of Nusantara Islam, 2021)
The purpose of this study was to describe the implementation of kyai policies in improving teacher performance in Islamic boarding schools. The method used is a descriptive method as a problem-solving procedure which is investigated by describing or describing the condition of the subject or object of research (a person, institution, society, etc.) at the present time based on visible facts, or as it should be. The results of the study illustrate that the kyai's policy in improving teacher performance at the Darul Muttaqien Parung Islamic Boarding School, Bogor is based on Panca Jiwa, which means Panca means five, soul means spirit, Pondok means boarding school institution, which substantively contains positive values that do not conflict with the teachings. Islamic teachings. The five spirits of the pesantren, namely; Sincerity, Simplicity, Independence, Ukhuwwah Islamiyyah and Freedom.